PENGEMBANGAN STRATEGI INFLUENCER MARKETING BAGI WEDDING ORGANIZER DALAM MEMBANGUN BRAND IMAGE DI MEDIA SOSIAL - Devisha Albania; Sugito (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2025)
The development of social media has encouraged wedding organizers to adopt more adaptive digital marketing strategies, one of which is influencer marketing. As service providers in the wedding industry, wedding organizers are required to build a strong brand image in order to remain competitive amid the rapid growth of the creative industry. However, the implementation of influencer marketing is often carried out without a structured and strategic approach. This community service activity focuses on developing influencer marketing strategies for wedding organizers in building brand image through social media platforms. The purpose of this program is to enhance the understanding and capacity of wedding organizers in designing, implementing, and evaluating effective influencer marketing strategies that align with their target market characteristics. The methods used include observation, social media analysis, strategic mentoring, and the formulation of influencer collaboration concepts based on relevance, credibility, and audience engagement. The empowerment strategy was implemented through collaborative content planning, appropriate influencer selection, and optimization of social media publications. The results indicate that a well-planned influencer marketing strategy can increase brand visibility, strengthen the professional image of the wedding organizer, and improve audience interaction on social media. Therefore, influencer marketing can serve as an effective and sustainable strategy for building the brand image of wedding organizers.